Spinocerebellar ataxia with axonal neuropathy type 1 revisited. (September 2019) - Scott, Patrick; Al Kindi, Adila; Al Fahdi, Amira; Al Yarubi, Naeema; Bruwer, Zandre; Al Adawi, Samir; Nandhagopal, Ramachandiran
Highlights: TDP1 mutation testing should be included in the diagnostic panel of recessive cerebellar ataxia with axonal neuropathy. The clinical spectrum of spinocerebellar ataxia with axonal neuropathy type 1 (SCAN1) includes mild cognitive deficits. Common founder mutation could account for the shared haplotype surrounding the TDP1 gene in the affected population. Abstract: Spinocerebellar ataxia with axonal neuropathy type 1 (SCAN1; OMIM #607250 ), an exceedingly rare disorder having been documented in only a single family from Saudi Arabia, is the result of an unusual mutation in the tyrosyl DNA phosphodiesterase 1 gene ( TDP1 ). We performed high-throughput sequencing (whole exome and ataxia gene panel) in two apparently unrelated Omani families segregating sensorimotor neuropathy and ataxia in an autosomal recessive fashion. Following validation by Sanger sequencing, all affected subjects (n = 4) were confirmed to carry the known SCAN1 pathogenic homozygous variant in the TDP1 gene, NM_001008744.1:c.1478A > G (p.His493Arg). In keeping with the initial description, our patients demonstrated progressive ataxia, cerebellar atrophy and disabling axonal sensori-motor neuropathy (n = 4), hypercholesterolemia (n = 2) and elevated serum alpha fetoprotein (n = 3). In addition, our patients also had mild cognitive deficits in multiple domains (n = 3), a feature not previously reported. Our findings independently revalidate the phenotype of TDP1 mutation and expand the clinical spectrum to include mild cognitive deficits. Haplotype sharing, as determined by DNA microarray (CytoScan HD), attests to a possible common founder mutation in the Arab population.